2018
DOI: 10.3389/fimmu.2018.01465
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Immune Response by the Inflammatory Metabolic Microenvironment in the Context of Allotransplantation

Abstract: Antigen challenge induced by allotransplantation results in the activation of T and B cells, followed by their differentiation and proliferation to mount an effective immune response. Metabolic fitness has been shown to be crucial for supporting the major shift from quiescent to active immune cells and for tuning the immune response. Metabolic reprogramming includes regulation of the balance between glycolysis and mitochondrial respiration processes. Recent research has shed new light on the functions served b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 114 publications
0
14
0
Order By: Relevance
“…Many of SRPK3-regulated transcripts encode proteins with functions in cellular metabolism or in the maintenance or biogenesis of mitochondria. In this regard, recent studies confirmed the importance of metabolic reprogramming as a 'gatekeeper' of B lymphocyte development, activation and responses (61)(62)(63)(64)(65). Loss of SRPK3 in MZ B cells results in differential splicing of candidate gatekeepers Nnt and Slc1a5.…”
Section: Discussionmentioning
confidence: 85%
“…Many of SRPK3-regulated transcripts encode proteins with functions in cellular metabolism or in the maintenance or biogenesis of mitochondria. In this regard, recent studies confirmed the importance of metabolic reprogramming as a 'gatekeeper' of B lymphocyte development, activation and responses (61)(62)(63)(64)(65). Loss of SRPK3 in MZ B cells results in differential splicing of candidate gatekeepers Nnt and Slc1a5.…”
Section: Discussionmentioning
confidence: 85%
“…Anaerobic glycolysis requires a lactate efflux mediated by proton‐coupled symporters or monocarboxylate transporters (MCT) and causes a pH decrease. The low external pH of the extracellular medium induces the inhibition of MCT‐mediated lactate efflux . This results in the accumulation of lactate inside the cells and subsequent inhibition of glycolytic enzyme activity through a feedback mechanism .…”
Section: Resultsmentioning
confidence: 99%
“…Excess lactate import into T cells has also been shown to restrict proliferation and cytokine production of CTLs. This is possibly due to their reliance on glycolysis [ 30 ], as lactate import goes along with consumption of reduced nicotinamide adenine dinucleotide (NADH) and inhibition of glycolysis [ 31 ]. On the other hand, Tregs are able to change their metabolism to function in a lactate-high environment, and are therefore unaffected [ 32 ].…”
Section: Expression and Importance Of Metabolite Transporters In Tmentioning
confidence: 99%